2018
DOI: 10.1038/s41598-018-25558-7
|View full text |Cite
|
Sign up to set email alerts
|

Large networks of rational agents form persistent echo chambers

Abstract: Echo chambers (ECs) are enclosed epistemic circles where like-minded people communicate and reinforce pre-existing beliefs. It remains unclear if cognitive errors are necessarily required for ECs to emerge, and then how ECs are able to persist in networks with available contrary information. We show that ECs can theoretically emerge amongst error-free Bayesian agents, and that larger networks encourage rather than ameliorate EC growth. This suggests that the network structure itself contributes to echo chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 26 publications
2
51
0
1
Order By: Relevance
“…We design our agents to be Bayesian not only because people's decisions can conform to Bayesian norms of rationality (e.g., Griffiths, Kemp, & Tenenbaum, 2008;Lewandowsky, Griffiths, & Kalish, 2009), but in particular because even seemingly "irrational" behaviors can emerge from Bayesian principles. For example, belief polarization Jern, Chang, & Kemp, 2009) can be accommodated within a rational Bayesian framework, and it has been shown that Bayesian agents can form persistent "echo chambers," enclosed epistemic bubbles in which agents share most beliefs (Madsen, Bailey, & Pilditch, 2018). The use of rational agents also seemed advisable in light of several suggestions that climate denial can be considered a rational enterprise Lewandowsky, Cook, & Lloyd, 2016), notwithstanding its wholesale dismissal of scientific evidence.…”
Section: Influence and Seepagementioning
confidence: 99%
“…We design our agents to be Bayesian not only because people's decisions can conform to Bayesian norms of rationality (e.g., Griffiths, Kemp, & Tenenbaum, 2008;Lewandowsky, Griffiths, & Kalish, 2009), but in particular because even seemingly "irrational" behaviors can emerge from Bayesian principles. For example, belief polarization Jern, Chang, & Kemp, 2009) can be accommodated within a rational Bayesian framework, and it has been shown that Bayesian agents can form persistent "echo chambers," enclosed epistemic bubbles in which agents share most beliefs (Madsen, Bailey, & Pilditch, 2018). The use of rational agents also seemed advisable in light of several suggestions that climate denial can be considered a rational enterprise Lewandowsky, Cook, & Lloyd, 2016), notwithstanding its wholesale dismissal of scientific evidence.…”
Section: Influence and Seepagementioning
confidence: 99%
“…Recently, a number of such simulations and computational models have been used to shed light on important issues in modern societies. For example, using computational cognitive models of belief revision in social networks, we may explore belief diffusion (Duggins, 2017), emergence of echo chambers (Madsen, Bailey, & Pilditch, 2018), belief cascading (Pilditch, 2017), and network pruning (Ngampruetikorn & Stephens, 2016).…”
Section: The Methodological Challengementioning
confidence: 99%
“…Whereas we may develop models to deal with isolated cognitive functions (e.g., memory retrieval, belief revision), the act of implementing models in relatively large social systems is useful in explicitly accounting for all aspects of the social system. For example, belief-revision models might require information-search strategies when dealing with social networks (see Madsen et al, 2018), and the nature of these strategies is made explicit in attempts to model them.…”
Section: The Methodological Challengementioning
confidence: 99%
“…Wagner, Paul M., and Tuomas Ylä-Anttila are among those researchers who believe that people and organizations tend to get information from those whose beliefs are similar to their own, forming "echo chambers" with their network connections. The effect of echo chambers has also been compared to epistemic circles and networks (Madsen, 2018), where like-minded people actively communicate and become increasingly entrenched in their beliefs.…”
Section: Cases and Their Analysismentioning
confidence: 99%